The Effectiveness of Using Comics in Efforts to Increase Adolescent Health Knowledge: A Literature Review - Septialti, Delita; Shaluhiyah, Zahroh; Widjanarko, Bagoes (Universitas Aisyah Pringsewu, 2022)
The use of media following the conditions of the audience or recipient of the message is one of the success factors in giving messages. Comics are one of the most effective media for adolescents. The display of comics with pictures and colours becomes one of their attractions. The simple language and funny stories make adolescents not feel bored when reading the comic. This study aims to determine the effectiveness of comics in increasing health knowledge in adolescents. The research method used is a literature review. Twenty articles have been filtered based on inclusion and exclusion criteria published between 2018-2022. The results show that comics can increase adolescent health knowledge, even for materials that are considered sensitive. Comics are an innovation in health promotion because they are not dull. The language of comics is simple enough for teenagers to analyze. It increases their motivation to learn because they do not pressure them. Comics do not only help teenagers but also help givers of material in facilitating delivery. In addition, acceptance from teenagers also encourages the use of comics as a medium for learning health. Comics are innovations in health media that effectively increase adolescent health knowledge, even for sensitive themes. It is recommended that health agencies use comics as an educational medium to facilitate the delivery of material. Abstrak: Pemilihan media yang sesuai dengan kondisi audiens atau penerima pesan menjadi salah satu faktor keberhasilan dalam pemberian pesan. Komik adalah salah satu media yang efektif bagi anak-anak. Dengan tampilan komik yang bergambar dan berwarna menjadi salah satu daya tarik bagi anak-anak. Selain itu bahasa komik yang sederhana dan cerita yang lucu membuat anak-anak tidak merasa bosan ketika membacanya. Penelitian ini bertujuan untuk mengetahui efektifitas komik dalam meningkatkan pengetahuan kesehatan pada remaja usia awal. Metode penelitian yang digunakan adalah literature riview terdapat 20 artikel yang sudah disaring berdasarkan kriteria inklusi dan ekslusi. Hasil penelitian menunjukkan bahwa penggunaan komik dapat meningkatkan pengetahuan kesehatan remaja, bahkan untuk materi yang dianggap sensistif. Komik menajdi inovasi dalam promosi kesehatan karena tidak membosankan bahasa komik cukup sederhana untuk dianalisis oleh remaja, meningkatkan motivasi belajar remaja karena tidak memberikan tekanan. Komik tidak hanya membantu remaja namun juga membantu pemberi materi dalam mempermudah penyampaian. Selain itu penerimaan dari remaja juga mendorong penggunaan komik sebagai media untuk belajar kesehatan. Sehingga dapat disimpulkan komik adalah inovasi dalam media kesehatan yang efektiv dalam meningkatkan pengetahuan kesehatan remaja bahkan untuk tema yang sensitive. Disarankan untuk instansi kesehatan menggunakan komik sebagai media edukasi untuk mempermudah penyampaian materi.